Spatially and temporally heterothermic kinetic model of hydrogen absorption and desorption in metals with heat transport. (22nd June 2022) - Nishi, Kengo; Uchikoshi, Takeru; Yamazaki, Jun; Nakashima, Yuki; Tanabe, Katsuaki
Abstract: Numerical modelling of hydrogen transport is effective for designing and optimizing various energy systems, including hydrogen storage devices, fuel cells, and nuclear fusion reactors. In the present study, we propose and demonstrate a spatiotemporally heterothermic, autonomous kinetic model of hydrogen absorption and desorption in metals for precise simulations. Our bidirectional transport model comprises elementary mass transfer processes of surface adsorption and desorption, subsurface transport, and bulk diffusion. Also implemented are heat generation and conduction stemming from the absorption enthalpy, to determine the evolution of temperature distribution in the metal body, as well as the hydrogen concentration profile. Simulations by our transport model reproduce experimental hydrogen absorption and desorption curves for various temperature levels and metal scales with a single identical set of numerical equations and kinetic parameters, to thus verify the validity of the model. Highlights: The first hydrogen absorption/desorption model with heat generation and transfer. Bidirectional applicability for both hydrogen absorption and desorption processes. Reproduction of a series of experimental data by numerical simulations. Highly useful for designing and optimizing various hydrogen energy systems.